Current Controversies in Clinical Management of Postmenopausal Osteoporosis - Kerschan-Schindl, K.; Mikosch, P.; Obermayer-Pietsch, B.; Gasser, R. W.; Dimai, H.-P.; Fahrleitner-Pammer, A.; Dobnig, H.; Roschger, P.; Preisinger, E.; Klaushofer, K.; Resch, H.; Pietschmann, P. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Osteoporosis is a frequent disease in postmenopausal women. Despite the fact that fragility fractures cause many problems – a bio-psycho-social burden for the individual and an economic burden for the society – osteoporosis is still underdiagnosed and undertreated. Controversies exist concerning assessment with different tools for initiating a disease-specific treatment, patient monitoring with bone turnover markers, and treatment duration due to potential side effects in long-term treatment. This manuscript outlines and discusses these controversies and the presented cases, representatives for frequent clinical problems, may give guidance for the clinician in deciding how and how long to treat his/her patient. Re-evaluations of the patients on a regular basis are essential to warrant the necessity of treatment continuation and may improve patients’ compliance.
Keywords: postmenopausal osteoporosis; bisphosphonate; long-term treatment; biomarkers; bone mineral density; bone mineralization density distribution